A new species of Heimbra Cameron, 1909 (Hymenoptera: Eurytomidae) from Eastern Uruguay - Perioto, Nelson W.; Lara, Rogéria I. R. (Entomological Communications, 2025)
A new species of Heimbra Cameron, 1909 (Hymenoptera, Eurytomidae) from eastern Uruguay, is described and illustrated. The species is diagnosed and differentiated from its congeners by the following combination of characters: mesopleuron contiguously punctate, appearing dull along the posterior margin; male tergite 7 lacking a transverse groove; and the mesoscutellum orange-brown laterally with a dorsal, longitudinal dark band. The description is based on four male specimens collected with Malaise traps in the municipality of Castillos, Departamento de Rocha, Uruguay. A revised key to the species of Heimbra, incorporating the newly described species, is provided. This discovery increases the number of known Heimbra species to nine and represents the second species of this genus recorded for Uruguay.